Os sentidos e significados sobre o trabalho do professor eventual: a construção de uma proposta com leitura - Silva, Cacilda Aparecida da (2010)
This research aims at understanding critically the construction process of meanings shared by a group of teachers from a public school of São Paulo concerning the job/ role of the substitute teacher. More specifically, this paper describes and discusses the substitute teacher activity, having as focuses two activity systems: understanding this professional s job at the school and developing a reading proposal as a support to the substitute teacher s job. To do so, meetings among the voluntary participants were carried out among titular teachers (this researcher among them), temporary teachers (OFAs), and substitute teachers. During the meetings, each participant expressed their point of view about the job/ role of the substitute teacher. The organization of this paper is based on the collaborative critical methodology (MAGALHÃES, 2006), in order to set a locus of critical collaboration aimed at a critical reflection about the actions of the participants on negotiating understandings and proposals which could provide transformation to the substitute teacher s reality in the context of the school. The study of the continuous academic background of this teacher as a collaborative and critical professional in the relationship with their partners is supported in the discussions of Vygotsky, Leontiev, Freire (1996); Engestrom (2009) LIBERALI( 2004 and 2008) and MAGALHÃES, (2004 and 2006), among others. As a result of the initial discussions, a proposal based on reading was begun, based on the Proposta Curricular do Estado de São Paulo (2008) and on the Projeto de Leitura nas Diversas areas do Conhecimento (LACE- fase 1,2002). The focus on reading was decided by the group of participant teachers, since one of the main focuses of the school in which most students have difficulties in reading and writing. The results show that: a) the initial meanings of the participants about the substitute teacher underwent some transformations except for one of the titular teachers who attended this research; b) the relations among people in the group of teachers led to a recognition of the importance of the HTP sessions use to discuss the theories which involve the teacher s practice; c) the discussed proposals have features of traditional teaching; d) the material initially developed isn t complied with the curricular proposal (2008) of São Paulo